2002
DOI: 10.1007/s00259-002-1065-1
|View full text |Cite
|
Sign up to set email alerts
|

Activity and practice of nuclear cardiology in the Czech Republic, 2001

Abstract: Radionuclide myocardial perfusion imaging (MPI) has been on the rise in Europe and the USA. Details on nuclear cardiology in the Czech Republic are not available as yet, as it is impossible to obtain comprehensive data from official registers owing to different methods of reporting and data evaluation. A questionnaire concerning nuclear cardiology activity and practice in 2001 was sent to all nuclear medicine departments in the Czech Republic. All 48 departments completed the questionnaire. In 2001, 50 planar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
1
0
2
Order By: Relevance
“…It is also found from the study that males were more prone to coronary artery diseases which are matched from previous study reported by Samad et al for male preponderance. Literature review also revealed that young female patients have lower mean value for coronary artery disease due to estrogen protective effects [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is also found from the study that males were more prone to coronary artery diseases which are matched from previous study reported by Samad et al for male preponderance. Literature review also revealed that young female patients have lower mean value for coronary artery disease due to estrogen protective effects [7].…”
Section: Discussionmentioning
confidence: 99%
“…Zavedení techniky gated SPECT, kterou v současnosti považujeme při zobrazování perfuze myokardu za standard, 1,2 kopírovalo v České republice vývoj v USA i v Evropě (obrázek 5). [3][4][5][6][7] Od roku 1998 jsou nukleárně kardiologické programy rovněž využívány k automatické kvantifi kaci rozsahu a závažnosti perfuzní abnormality pomocí segmentárního skórovacího systému. Významně se také mění spektrum pacientů odesílaných na vyšetření touto metodou.…”
Section: úVodunclassified
“…[5][6][7][8] Rovněž v České republice je SPECT myokardu s počtem cca 17 000 vyšetření ročně nejčastější zátěžovou zobrazovací metodou. 3,6,7 V posledních deseti letech byly původně jednodetektorové SPECT kamery postupně nahrazovány dvoudetektorovými kamerami s variabilním uspořádáním detektorů (obrázek 1). Lze tak za stejnou dobu nastřádat dvojnásobnou hustotu impulsů a získat významně kvalitnější gated SPECT obrazy.…”
Section: End-systolaunclassified